A Measure of Islamophobia. Issue 1 (1st April 2014) - S. Sayyid
Abstract : The growing literature on Islamophobia is dominated by empirical studies, the analysis of media representations and socio-psychological approaches, while many of these studies have been valuable in illustrating the range of expressions of Islamophobia; they have been less successful in understanding the phenomena, and mapping its relationship with other forms of discriminatory practices such as racism and anti-Semitism. This article presents a conceptual examination of the category of Islamophobia and the work it is called upon to do in contemporary debates, as prelude to a discussion about what a theorization of this concept could contribute to the field of social analysis and policy.